Efektivitas Wrist Stretching, Tendon and Nerve Gliding Exercise dalam Menurunkan Nyeri dan Meningkatkan Fungsional Wrist pada Kasus Carpal Tunnel Syndrome - Cici Anggraini; Rahmi Windhy Astari (Syntax Corporation Indonesia, 2021)
Carpal Tunnel Syndrome (CTS) is a medianus nerve clamp due to entrapment neuropathy when going through the carpal tunnel in the wrist precisely under the flexor retinaculum. The goal of this study is to find out the effectiveness of wrist stretching, tendon and nerve gliding exercise in reducing pain and improving functional wrist in people with Carpal Tunnel Syndrome. To find out the effectiveness of wrist stretching, tendon and nerve in reducing pain and improving functional wrist in cases of Carpal Tunnel Syndrome. A 58-year-old woman with a job before the doughnut seller pandemic. Patients complain of pain in the wrist spreading and feel tingling / numbness in the fingers 1-3, the fingers feel stiff and difficult to shake. Patients therapy for 2x / week in 3 weeks, one patient therapy followed for 20-30 minutes. Patients are given therapy in the form of wrist stretching, tendon and nerve gliding exercise. Pain was measured using numeric rating scale (NRS) and Boston Carpal Tunnel Questionair (BCTQ) for the severity of CTS. After therapy was given the result of a decrease in press pain and motion pain by 1 point, and there was a slight improvement in the functional ability of the wrist measured using BCTQ. The provision of therapy in the form of wrist stretching, tendon and nerve gliding exercise can reduce pain and improve the functional ability of the wrist.